Properties of concrete and structural behaviour of reinforced concrete beam containing shredded waste paper as an additive - Solahuddin, Azuwa; Fadzil, Mat Yahaya (Springer Nature Korea, 2023)
This research uses WP to investigate the effect of two types of Shredded Waste Paper (SWP) comprising Shredded Copier Waste Paper (SCPWP) and Shredded Cardboard Waste Paper (SCBWP) as additives on the properties of concrete and the structural behaviour of Reinforced Concrete Beam (RCB). The slump, compressive, flexural, and splitting tensile strengths increase by 4–13% for 5–10% addition of SCPWP and decrease by 16–23% for 15% addition of SCPWP compared to 0% addition. For SCBWP, the slump, compressive, flexural and splitting tensile strengths increase by 10–23% for 5–10% addition and decrease by 15–21% for 15% addition compared to 0% addition. 15% of SCPWP and SCBWP addition records the highest effect in water absorption and efflorescence, showing 11% and 10.28% increases with 15% addition of SCBWP and SCPWP. Scanning electron microscope (SEM) analysis reveals that the crack is repaired, and the presence of calcium hydroxide (Ca(OH)2) and calcium–silicate–hydrate (C–S–H) links enhances the concrete strength. The addition of 10% SCPWP and 10% SCBWP in the concrete mixtures improves the structural behaviour of RCB with stirrup spacing (SS) = 100 mm (full), 150 mm and 200 mm (reduced) by increasing the load and reducing the deflection. Apart from that, the concrete bending and shear strains also increase by 44.17% and 34.9%. The failure mode of the RCB changes from shear to bending. This study indicates that SCPWP and SCBWP can be used as additives in concrete at 5% and 10%, and 10% for RCB with significant strength and structural improvement.